Upaya Efektif dalam Pembinaan dan Pembimbingan Narapidana Hamil di Lembaga Pemasyarakatan - Subroto, Mitro; Deffrilia, Djuwita (Universitas Pahlawan Tuanku Tambusai, 2024)
The correctional system in Indonesia, based on Pancasila and the 1945 Constitution, emphasizes not only punishment but also aims to facilitate the social reintegration of inmates. This study examines the rehabilitation of female inmates, particularly those who are pregnant or nursing, who possess additional rights to ensure the well-being of both mother and child. A tailored rehabilitation approach aims to reduce stress and meet the specific needs of female inmates. The research employs a library research method, reviewing literature and data from various sources related to the rehabilitation of pregnant inmates, alongside qualitative analysis to evaluate existing policies. The findings indicate that rehabilitation in correctional facilities includes skills development activities such as cooking, crafts, agriculture, and vocational training, aimed at preparing inmates for life after release. However, challenges remain in implementing these programs, including limitations in facilities, budget constraints, and insufficient human resources. In conclusion, there is a need to enhance infrastructure and diversify rehabilitation programs to ensure that each inmate receives appropriate rehabilitation tailored to their needs. Rehabilitation that considers the unique conditions and needs of female inmates can support their rehabilitation and reintegration process, enabling them to contribute responsibly as members of society.